Ceramic artificial bone material and preparation method thereof
By using a PEG-PLA micelle system and gradient sintering process, a three-dimensional interconnected microporous structure was constructed, which solved the problems of low porosity and poor connectivity of traditional hydroxyapatite ceramic materials, and improved the mechanical properties and osseointegration efficiency of the material.
Patent Information
- Application Number
- CN202511493610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-10-20
AI Technical Summary
Traditional hydroxyapatite ceramic materials have low porosity and poor connectivity, which cannot provide three-dimensional space for the growth of new bone cells. Furthermore, the macroporous structure can easily lead to a decline in the mechanical properties of the material. Existing pore-forming agents have poor compatibility with precursors, resulting in uneven pore distribution and affecting the uniformity of material composition and mechanical properties.
An amphiphilic micelle system formed by PEG-PLA block copolymer was used to regulate the dispersion of pore-forming agents and the powder growth environment through micelle solution. Combined with gradient sintering process, a microporous structure was constructed to solve the compatibility problem between pore-forming agents and precursors, thereby achieving uniform pore distribution and material composition.
It achieves a three-dimensionally connected and uniformly distributed microporous structure, which improves the mechanical properties and osseointegration efficiency of the material, avoids the problem of decreased mechanical properties of macroporous structures, and meets the needs of clinical bone repair.
Smart Images

Figure CN120943623A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic material preparation technology, specifically relating to a ceramic artificial bone material and its preparation method. Background Technology
[0002] Hydroxyapatite (HA) ceramics, due to their chemical composition and crystal structure being highly compatible with the inorganic components of human bone tissue, possess excellent biocompatibility, osteoconductivity, and biodegradability, making them a commonly used artificial bone repair material in clinical practice. Among them, multi-doped hydroxyapatite (such as Sr...) 2+ Mg 2+ Si 4+ Doping with HA can regulate the degradation rate and osteoinductive activity of materials through ionic synergy, matching the human bone healing cycle, and has become a research hotspot in the field of biomedical materials in recent years.
[0003] However, hydroxyapatite ceramics prepared by traditional methods have a dense structure, generally low porosity, and are mainly composed of isolated closed pores with poor connectivity. This makes it difficult to provide a three-dimensional space for the growth of new bone cells and to facilitate the transport of nutrients and the excretion of metabolic products, resulting in low bone integration efficiency and limiting its application in key scenarios such as the repair of weight-bearing bone defects.
[0004] Large-pore structures are usually obtained through porous scaffold molds. However, while large pores can enhance the growth and osseointegration of implants after bone-in surgery, they can also lead to problems such as excessively rapid degradation, inability of new bone to replace them in time, gaps in the material structure, and excessively rapid decline in mechanical properties.
[0005] Therefore, micropores (pore size <10 µm) play a crucial role in bone regeneration and the presence of cells or nutrients. Micropores provide a larger surface area. Commonly used pore-forming agents in existing techniques include ammonium bicarbonate and polymethyl methacrylate (PMMA) microspheres. However, the thermal decomposition of ammonium bicarbonate easily generates intense localized gas production, leading to uneven pore sizes and the formation of through-cracks, reducing the material's mechanical strength. While PMMA microspheres can form regular pores, their highly hydrophobic surface results in poor compatibility with the hydrophilic hydroxyapatite precursor slurry, leading to microsphere aggregation and sedimentation, resulting in a disordered pore distribution and an inability to construct a connected porous structure that matches human bone trabeculae. Furthermore, the hydroxyapatite powder and dopant ions in the precursor slurry are prone to aggregation due to localized concentration differences, affecting the material's compositional uniformity and mechanical property stability, making it difficult to meet clinical bone repair needs. Summary of the Invention
[0006] This invention provides a ceramic artificial bone material and its preparation method. By introducing an amphiphilic micelle system to regulate the dispersion of the pore-forming agent and the powder growth environment, and combined with precise process design, problems such as poor compatibility between the pore-forming agent and the precursor, powder agglomeration, and uneven pore structure are solved, ultimately obtaining a ceramic artificial bone material with microporous structure, high porosity, and good connectivity.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a ceramic artificial bone material includes the following steps: S1. Preparation of micelle solution: Dissolve 0.8~1.2g of polyethylene glycol-polylactic acid (PEG-PLA) block copolymer in 15~20mL of dichloromethane and stir until homogeneous; separately, mix 8%-12% (w / w) aqueous ethanol solution with the above PEG-PLA dichloromethane solution at a volume ratio of 5:1, and stir continuously at 300-400r / min during the dropwise addition. After the dropwise addition is complete, continue stirring for 30-60min. Remove the dichloromethane by evaporation to form a stable PEG-PLA micelle system and obtain the micelle solution. S2, Preparation of precursor slurry: 8-10g of hydroxyapatite powder, 0.3-0.5mmol of strontium nitrate (Sr(NO3)2), 0.1-0.2mmol of magnesium nitrate (Mg(NO3)2·6H2O), 0.2-0.4mmol of tetraethyl orthosilicate (TEOS), and citric acid are added to 2 / 3 of the micelle solution in S1; wherein, citric acid and total metal ions (Sr... 2+ Mg 2+ The molar ratio of the precursor slurry to the slurry is 1.3-1.7:1, and 30-40 mL of deionized water is added simultaneously. The mixture is stirred at 25-30℃ and 200-300 r / min for 30-40 min to obtain a uniform precursor slurry. S3. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S2, weigh PLGA microspheres at a mass ratio of 0.3-0.5:1, add them to the 1 / 3 micelle solution reserved in S1, and ultrasonically disperse for 50-70 min to obtain a PLGA microsphere suspension; after the precursor slurry is stirred, maintain it at 200 r / min and add the PLGA microsphere suspension dropwise at a rate of 2-4 drops / second, and continue stirring for 25-35 min to form a composite slurry; S4. Molding and Drying: Molding and Drying: Inject the composite slurry into a polyethylene mold and dry it in a vacuum drying oven at 40-50℃ for 12-16 hours to remove free moisture and obtain a green body. S5. Gradient sintering: The green body is placed in a high-temperature sintering furnace and heated to 500-600℃ at a rate of 3-5℃ / min and held for 2-3 hours to remove pore-forming agents, micelles and organic additives; then the temperature is increased to 750-850℃ at a rate of 2-3℃ / min and held for 4-5 hours to promote crystal densification; finally, it is cooled to room temperature with the furnace to obtain a ceramic artificial bone material.
[0008] The core innovations of this invention specifically include: Dual-effect micelle regulation mechanism: The amphiphilic micelle system formed by PEG-PLA block copolymer plays a dual role: On the one hand, the hydrophilic PEG segments are compatible with the precursor slurry, and the hydrophobic PLA segments combine with PLGA microspheres to build an interfacial bridge. Combined with ultrasonic dispersion, it breaks the van der Waals forces between microspheres and solves the compatibility problem between the pore-forming agent and the slurry. On the other hand, micelles can encapsulate hydroxyapatite powder and doped ions, inhibiting particle agglomeration through steric hindrance effect, while ensuring uniform distribution of ions in the system and guaranteeing the uniformity of material composition.
[0009] The micelle solution is first used to prepare the precursor slurry to ensure uniform dispersion of powder and ions; then it is used to disperse the pore-forming agent. After the viscosity of the precursor system is stable, it is precisely added dropwise to avoid competition between powder and microspheres for dispersion, prevent microspheres from settling, and achieve orderly distribution of pores, similar to the advantages of colloidal crystal template method in regulating pore structure.
[0010] The low-temperature stage slowly removes pore-forming agents and micelles to avoid violent gas generation that could damage the structure; the high-temperature stage promotes orderly crystal growth, improving mechanical properties while ensuring high porosity, thus solving the problem of balancing the strength and structure of porous materials.
[0011] The advantages of this invention compared to the prior art (1) By using PEG-PLA micelle regulation and a phased process, a three-dimensional interconnected and uniformly distributed microporous structure (pore size adapted to cell growth and material transport) was constructed, which not only solved the problem of "no growth space" in traditional dense HA ceramics, but also avoided the defect of "degradation faster than bone formation" in simple macroporous structures.
[0012] (2) Amphiphilic PEG-PLA micelles act as "interfacial bridges," with their hydrophilic segments compatible with the hydrophilic precursor slurry and their hydrophobic segments binding with the PLGA pore-forming agent. Combined with ultrasonic dispersion, this thoroughly eliminates the aggregation of the pore-forming agent. Simultaneously, the micelles encapsulate HA powder and doped ions (Sr) through steric hindrance. 2+ Mg 2+ Si 4+ This ensures uniform material composition and avoids the instability of mechanical properties caused by disordered pores and localized component imbalances in traditional processes. Attached Figure Description
[0013] Figure 1These are the Fourier transform infrared spectra of the ceramic artificial bone materials prepared in Examples 1-3 and Comparative Example 1; Figure 2 These are high-powered microscopic images of the ceramic artificial bone material prepared in Example 1; Figure 3 These are low-power microscopic images of the ceramic artificial bone material prepared in Example 1; Figure 4 This is a photograph of the ceramic artificial bone material prepared in Example 1; Figure 5 This is a microscope image of the ceramic artificial bone material prepared in Comparative Example 1. Detailed Implementation
[0014] To make the above-mentioned objectives, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to examples. The following content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, as long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.
[0015] The preparation method of the present invention will be described below through specific embodiments and comparative examples.
[0016] Example 1 A method for preparing a ceramic artificial bone material includes the following steps: S1. Preparation of micelle solution: Dissolve 0.8g PEG-PLA in 15mL dichloromethane and stir until homogeneous; separately, mix 8% (w / w) aqueous ethanol solution with the above PEG-PLA dichloromethane solution at a volume ratio of 5:1. During the dropwise addition, stir continuously at 300r / min. After the dropwise addition is complete, continue stirring for 30min. Remove the dichloromethane by evaporation to form a stable PEG-PLA micelle system and obtain the micelle solution. S2, Preparation of precursor slurry: 8g hydroxyapatite powder, 0.3mmol Sr(NO3)2, 0.1mmol Mg(NO3)2·6H2O, 0.2mmol TEOS and citric acid were added to 2 / 3 of the micelle solution in S1; wherein, citric acid and total metal ions (Sr 2+ Mg 2+ The molar ratio of the precursor slurry to the slurry was 1.3:1, and 30 mL of deionized water was added. The mixture was stirred at 25 °C and 200 r / min for 30 min to obtain a uniform precursor slurry. S3. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S2, weigh PLGA microspheres at a mass ratio of 0.3:1 (hydroxyapatite powder: PLGA microspheres), add them to the 1 / 3 micelle solution reserved in S1, and ultrasonically disperse for 50 min to obtain a PLGA microsphere suspension; after the precursor slurry is stirred, maintain the stirring state at 200 r / min, add the PLGA microsphere suspension dropwise at a rate of 2 drops / second, and continue stirring for 25-35 min to form a composite slurry; S4. Molding and Drying: Molding and Drying: Inject the composite slurry into a polyethylene mold and dry it in a vacuum drying oven at 40℃ for 12 hours to remove free moisture and obtain a green body; S5. Gradient sintering: The green body is placed in a high-temperature sintering furnace and heated to 500°C at a rate of 3°C / min and held for 2 hours to remove pore-forming agents, micelles and organic additives; then heated to 750°C at a rate of 2°C / min and held for 4 hours to promote crystal densification; finally cooled to room temperature with the furnace to obtain a ceramic artificial bone material.
[0017] Example 2 A method for preparing a ceramic artificial bone material includes the following steps: S1. Preparation of micelle solution: Dissolve 1.0 g PEG-PLA in 18 mL dichloromethane and stir until homogeneous; separately, mix 10% (w / w) aqueous ethanol solution with the above PEG-PLA dichloromethane solution at a volume ratio of 5:1. During the dropwise addition, stir continuously at 350 r / min. After the dropwise addition is complete, continue stirring for 40 min. Remove the dichloromethane by evaporation to form a stable PEG-PLA micelle system and obtain the micelle solution. S2, Preparation of precursor slurry: 9g hydroxyapatite powder, 0.4mmol Sr(NO3)2, 0.15mmol Mg(NO3)2·6H2O, 0.3mmol TEOS and citric acid were added to 2 / 3 of the micelle solution in S1; wherein, citric acid and total metal ions (Sr 2+ Mg 2+ The molar ratio of the precursor slurry to the slurry was 1.5:1, and 35 mL of deionized water was added. The mixture was stirred at 28 °C and 300 r / min for 35 min to obtain a uniform precursor slurry. S3. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S2, weigh PLGA microspheres at a mass ratio of 0.4:1 and add them to the 1 / 3 micelle solution reserved in S1. Disperse ultrasonically for 60 min to obtain a PLGA microsphere suspension. After the precursor slurry is stirred, keep it at 200 r / min and add the PLGA microsphere suspension dropwise at a rate of 3 drops / second. Continue stirring for 30 min to form a composite slurry. S4. Molding and Drying: Molding and Drying: Inject the composite slurry into a polyethylene mold and dry it in a vacuum drying oven at 45℃ for 14 hours to remove free moisture and obtain a green body; S5. Gradient sintering: The green body is placed in a high-temperature sintering furnace and heated to 550°C at a rate of 4°C / min and held for 2.5 hours to remove pore-forming agents, micelles and organic additives; then heated to 800°C at a rate of 2°C / min and held for 4 hours to promote crystal densification; finally cooled to room temperature with the furnace to obtain a ceramic artificial bone material.
[0018] Example 3 A method for preparing a ceramic artificial bone material includes the following steps: S1. Preparation of micelle solution: Dissolve 1.2g of PEG-PLA in 20mL of dichloromethane and stir until homogeneous; separately, mix 12% (w / w) aqueous ethanol solution with the above PEG-PLA dichloromethane solution at a volume ratio of 5:1. During the dropwise addition, stir continuously at 400r / min. After the dropwise addition is complete, continue stirring for 60min. Remove the dichloromethane by evaporation to form a stable PEG-PLA micelle system and obtain the micelle solution. S2, Preparation of precursor slurry: 10g hydroxyapatite powder, 0.5mmol Sr(NO3)2, 0.2mmol Mg(NO3)2·6H2O, 0.4mmol TEOS and citric acid were added to 2 / 3 of the micelle solution in S1; wherein, citric acid and total metal ions (Sr 2+ Mg 2+ The molar ratio of the precursor slurry to the slurry was 1.7:1, and 40 mL of deionized water was added. The mixture was stirred at 30 °C and 300 r / min for 40 min to obtain a uniform precursor slurry. S3. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S2, weigh PLGA microspheres at a mass ratio of 0.5:1 and add them to the 1 / 3 micelle solution reserved in S1. Disperse ultrasonically for 70 min to obtain a PLGA microsphere suspension. After the precursor slurry is stirred, keep it at 200 r / min and add the PLGA microsphere suspension dropwise at a rate of 4 drops / second. Continue stirring for 35 min to form a composite slurry. S4. Molding and Drying: Molding and Drying: Inject the composite slurry into a polyethylene mold and dry it in a vacuum drying oven at 50℃ for 16 hours to remove free moisture and obtain a green body. S5. Gradient sintering: The green body is placed in a high-temperature sintering furnace and heated to 600°C at a rate of 5°C / min and held for 3 hours to remove pore-forming agents, micelles and organic additives; then heated to 850°C at a rate of 3°C / min and held for 5 hours to promote crystal densification; finally cooled to room temperature with the furnace to obtain a ceramic artificial bone material.
[0019] Comparative Example 1 A method for preparing a ceramic artificial bone material includes the following steps: S1. Preparation of precursor slurry: 8g of hydroxyapatite powder, 0.3mmol Sr(NO3)2, 0.1mmol Mg(NO3)2·6H2O, 0.2mmol TEOS and citric acid were added to 30mL of deionized water; the mixture was stirred at 25℃ and 200r / min for 30min to obtain a uniform precursor slurry. S2. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S1, weigh PLGA microspheres according to a mass ratio of hydroxyapatite powder to PLGA microspheres of 0.3:1, add 30 mL of 12% ethanol aqueous solution, and ultrasonically disperse for 50 min to obtain PLGA microsphere suspension; after the precursor slurry is stirred, maintain it at 200 r / min and add PLGA microsphere suspension dropwise at a rate of 2 drops / second, and continue stirring for 25-35 min to form composite slurry; S3. Molding and Drying: Molding and Drying: Inject the composite slurry into a polyethylene mold and dry it in a vacuum drying oven at 40℃ for 12 hours to remove free moisture and obtain a green body; S4. Gradient sintering: The green body is placed in a high-temperature sintering furnace and heated to 500°C at a rate of 3°C / min and held for 2 hours; then heated to 750°C at a rate of 2°C / min and held for 4 hours to promote crystal densification; finally, it is cooled to room temperature with the furnace to obtain a ceramic artificial bone material.
[0020] Figure 1 These are the Fourier transform infrared spectra of the ceramic artificial bone materials prepared in Examples 1-3 and Comparative Example 1; the characteristic peak of hydroxyapatite (HA) in the spectra of Examples 1-3 and Comparative Example 1.
[0021] Figure 2 These are high-powered microscopic images of the ceramic artificial bone material prepared in Example 1. Microscopic images are used to directly observe the microscopic pore morphology of the material. The images show a large number of micropores with a diameter <10 μm, forming a three-dimensional interconnected network with uniform size (no significant size difference), and no isolated closed pores or localized dense / vacant pores. This is because the hydrophilic segments of the PEG-PLA micelles are compatible with the precursor, while the hydrophobic segments combine with the PLGA pore-forming agent. Combined with ultrasonic dispersion, this breaks up microsphere aggregation, resulting in a uniform distribution of the pore-forming agent. Furthermore, the micelles first disperse the powder and ions, then disperse the pore-forming agent, avoiding microsphere sedimentation caused by competitive dispersion between the two, ultimately forming an ordered and interconnected microporous structure.
[0022] Figure 3These are low-power microscopic images of the ceramic artificial bone material prepared in Example 1; it can be seen that there are no obvious cracks on the surface of the artificial bone material over a large area.
[0023] Figure 4 The image shows a photograph of the ceramic artificial bone material prepared in Example 1; the material surface has no obvious cracks or deformation, and the color is uniform.
[0024] Figure 5 The image shows a microscope image of the ceramic artificial bone material prepared in Comparative Example 1. As a blank control, it can be seen that the artificial bone material is difficult to shape, which is due to uneven internal stress caused by agglomeration during the heating process.
Claims
1. A method for preparing a ceramic artificial bone material, characterized in that, Includes the following steps: S1. Preparation of micelle solution: Dissolve PEG-PLA block copolymer in dichloromethane and stir until homogeneous; separately, mix aqueous ethanol solution with the above PEG-PLA dichloromethane solution at a volume ratio of 5:1, and continue stirring during the dropwise addition. After the dropwise addition is complete, continue stirring to remove dichloromethane by evaporation, forming a stable PEG-PLA micelle system and obtaining a micelle solution. S2, Preparation of precursor slurry: Hydroxyapatite powder, Sr(NO3)2, Mg(NO3)2·6H2O, positive TEOS and citric acid are added to 2 / 3 of the micelle solution in S1; wherein, citric acid reacts with the total metal ions Sr2+ and Mg2+. 2+ The molar ratio is 1.3-1.7:1, and deionized water is added simultaneously; the mixture is stirred at 25-30℃ to obtain a uniform precursor slurry; S3. Pretreatment and addition of pore-forming agent: Based on the mass of hydroxyapatite powder in S2, weigh PLGA microspheres at a mass ratio of 0.3-0.5:1, add them to the 1 / 3 micelle solution reserved in S1, and disperse them by ultrasonication to obtain a PLGA microsphere suspension; after the precursor slurry is stirred, keep stirring and add the PLGA microsphere suspension dropwise, continue stirring to form a composite slurry; S4. Molding and Drying: The composite slurry is injected into a polyethylene mold and dried in a vacuum drying oven to remove free moisture and obtain a green body; S5. Gradient sintering: The green body is placed in a high-temperature sintering furnace, first heated to 500-600℃ and held; then heated to 750-850℃ and held; finally cooled to room temperature with the furnace to obtain ceramic artificial bone material.
2. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, The amount of PEG-PLA block copolymer added in S1 is 0.8~1.2g, the amount of dichloromethane is 15~20mL, the mass fraction of ethanol aqueous solution is 8%-12%, the stirring rate during the dropwise addition process is 300-400r / min, and the stirring time after dropwise addition is 30-60min.
3. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, The amount of hydroxyapatite powder added in S2 is 8-10g, the amount of Sr(NO3)2 added is 0.3-0.5mmol, the amount of Mg(NO3)2·6H2O added is 0.1-0.2mmol, the amount of TEOS added is 0.2-0.4mmol, and the amount of deionized water is 30-40mL.
4. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, As described in S2, stirring is carried out at 25-30℃, with a stirring rate of 200-300 r / min and a stirring time of 30-40 min.
5. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, The ultrasonic dispersion time described in S3 is 50-70 min, the stirring rate of the precursor slurry is maintained at 200 r / min, the dropping acceleration rate of the PLGA microsphere suspension is 2-4 drops / second, and the stirring time after dropping is 25-35 min.
6. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, The temperature of the vacuum drying oven described in S4 is 40-50℃, and the drying time is 12-16h.
7. The method for preparing ceramic artificial bone material according to claim 1, characterized in that, The heating rate to 500-600℃ described in S5 is 3-5℃ / min, and the holding time is 2-3h; the heating rate to 750-850℃ is 2-3℃ / min, and the holding time is 4-5h.
8. A ceramic artificial bone material obtained by any one of the preparation methods described in claims 1-7.
Citation Information
Patent Citations
Partially bioabsorbable implant
CN101610797A
Calcium phosphate nano-structure hollow microsphere and preparation method thereof
CN101759169A
Two-dimensional single-layer highly-ordered mesoporous TiO2 nano net material as well as preparation method and application thereof
CN119581546A
Star-shaped polyoxazoline, colloidal particle and their production method
JP2003261678A
Porous microsphere and manufacturing method thereof
KR1020100138128A
Cited By
Energy-saving and environment-friendly treatment method for spinning electrostatic deoiling sewage
CN121181110A